2010
DOI: 10.1002/adma.200902295
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Formation and Mechanical Characterization of Metallic Glassy Nanowires

Abstract: Extraordinary flexible, very long, and individual amorphous nanowires composed of metallic glasses are produced by the drawing process based on superplastic deformation above the glass transition temperature. The outstanding mechanical properties of metallic glasses including low Young's modulus and high strength can be inherited in nanowire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…Bulk metallic glasses are quite stable in the supercooled state and, after thermal processing, can be slowly cooled back to the strong glassy state with negligible volume shrinkage. Th is outstanding thermal formability of BMGs has recently been exploited for applications in nanotechnology and MEMS [71][72][73][74][75][76][77][78].…”
Section: Nanotechnology and Memsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk metallic glasses are quite stable in the supercooled state and, after thermal processing, can be slowly cooled back to the strong glassy state with negligible volume shrinkage. Th is outstanding thermal formability of BMGs has recently been exploited for applications in nanotechnology and MEMS [71][72][73][74][75][76][77][78].…”
Section: Nanotechnology and Memsmentioning
confidence: 99%
“…Sputtered BMG fi lms have also been used to fabricate actuators and micro-cantilevers for MEMS applications [74]. Recently, the dimensions of BMG patterns and parts have been further reduced to scales on the order of tens of nanometers by superplastic deformation [76] and thermoplastic forming [78,79]. Metallic glass nanowires fabricated by these methods show interesting multi-harmonic oscillations with possible applications in mechanical and magnetic sensors.…”
Section: Nanotechnology and Memsmentioning
confidence: 99%
“…The formation of localized shear bands strongly compromises the practical usages of the metallic glasses for load-bearing applications. One promising way to overcome this shortcoming of metallic glasses is to reduce the sample size of MGs using Focused Ion Beam (FIB) [3] or hot extension [4]. It has been shown that MG in the form of nanowires can exhibit large tensile strain [5,6].…”
mentioning
confidence: 99%
“…Growing number of research activities are now focused on metallic glassy nanoobjects, for example, nanowires [59,60]. Nanowires have been used as barcodes for biological multiplexing, which could be visualized by an optical microscope [61].…”
Section: Direct Formation Of a Nanostructure On Depositionmentioning
confidence: 99%